Debating patriarchy the Hindu Code Bill controversy in India (1941-1956) - Sinha, Chitra (New Delhi : Oxford University Press, 2012)
Through an analysis of the controversial Hindu Code Bill, this book explores the formative process of Indian law. It examines the family law reforms in India to understand the connection between legal reforms and social transformation.
Description based on online resource; title from PDF title page (viewed on Aug. 24, 2012).
Includes bibliographical references and index.
Keywords: Hindus -- Legal status, laws, etc. -- India; Domestic relations -- India; Law reform -- India -- History